Effects of Light Intensity and Seedling Mediaon The Growth of Reutealis Trisperma (Blanco) Airy Shaw Seedling - Wardiana, Edi; Herman, Maman (AGRIVITA Journal of Agricultural Science, 2011)
This experiment was conducted at Pakuwon Experimental Station with altitude about 450 m above sea level and Latosol type of soil beginning from January until June 2009. It aimed to investigate the effect of light intensity and seedling media on growth of "Sunan" candle nut (R. trisperma) seedling. Split plot design with 4 replications was used in this study. The main plots factor are percentage of light intensity (I) consisted of two levels : I1 (65%) and I2 (100%), and the split plots factor are seedling media (M) consisted of five kinds of media: M1 (50% soil and 50% sheep dung), M2 (50% soil and 50% rice husk), M3 (50% sheep dung and 50% rice husk), M4 (33.3% soil, 33.3% sheep dung, and 33.3% rice husk), and M5 (100% soil). Result showed that: (1) for better growth of R. trisperma seedling suggested to be shaded, and (2) mixed of the 50% soil and 50% sheep dung are the best media for it growth. Keywords: Reutealis trisperma (Blanco) Airy Shaw, light intensity, seedling media, organic matter